Clinical significance of autoantibodies in a large cohort of patients with chronic graft‐versus‐host disease defined by NIH criteria. Issue 2 (24th November 2014) - Kuzmina, Zoya; Gounden, Verena; Curtis, Lauren; Avila, Daniele; RNP, Tiffani Taylor; Baruffaldi, Judy; Cowen, Edward W.; Naik, Haley B.; Hasni, Sarfaraz A.; Mays, Jacqueline W.; Mitchell, Sandra; Baird, Kristin; et al.
<x xml:space="preserve">Abstract</x> There is an unmet need for identifying new clinical biomarkers in chronic Graft‐versus‐Host‐disease (cGVHD) suitable for diagnosis and disease monitoring. Circulating autoantibodies represent an ongoing immune response and suggest a pathogenic role for B cells in cGVHD. Autoantibodies could be useful markers of cGVHD disease activity, severity, or organ specificity; however, their clinical utility is not established. The focus of this study was to determine the incidence and associations of a broad array of clinical autoantibodies with cGVHD manifestations in a large patient cohort characterized by NIH criteria. A panel of 21 circulating antibodies commonly used in clinical medicine was tested in 280 cGVHD patients (70% severe) enrolled in a cross‐sectional prospective natural history study. Median cGVHD duration was two years. Patients with circulating autoantibodies (62%) had significantly higher levels of IgM (P < 0.0001), IgG (P < 0.0001), and IgA (P = 0.001), elevated uric acid (P = 0.008) and total protein (P = 0.0004), and higher numbers of CD3+ (P = 0.002), CD4+ (P = 0.001), CD8+ (P = 0.023) T cells, and CD19+ B cells (P < 0.0001). Multiple antibodies were detected in 35% of patients. Prior rituximab therapy (n = 66) was associated with reduced presence of autoantibodies (48 vs. 66% P = 0.01). Only oral cGVHD was significantly associated with presence of autoantibodies in this study (P = 0.028). No significant associations were found between cGVHD activity and severity, and presence of autoantibodies. Circulating autoantibodies are common in patients with advanced cGVHD. Their presence is associated with better quantitative immunologic reconstitution but does not have utility as a clinical biomarker of cGVHD. Am. J. Hematol. 90:114–119, 2015. © 2014 Wiley Periodicals, Inc.